Prokineticin 2 potentiates acid-sensing ion channel activity in rat dorsal root ganglion neurons - Qiu Chun-Yu; Liu Yu-Qiang; Qiu Fang; Wu Jiliang; Zhou Qun-Yong; Hu Wang-Ping (Journal of Neuroinflammation, 2012)
Abstract Background Prokineticin 2 (PK2) is a secreted protein and causes potent hyperalgesia in vivo, and is therefore considered to be a new pronociceptive mediator. However, the molecular targets responsible for the pronociceptive effects of PK2 are still poorly understood. Here, we have found that PK2 potentiates the activity of acid-sensing ion channels in the primary sensory neurons. Methods In the present study, experiments were performed on neurons freshly isolated from rat dorsal root ganglion by using whole-cell patch clamp and voltage-clamp recording techniques. Results PK2 dose-dependently enhanced proton-gated currents with an EC50 of 0.22 ± 0.06 nM. PK2 shifted the proton concentration-response curve upwards, with a 1.81 ± 0.11 fold increase of the maximal current response. PK2 enhancing effect on proton-gated currents was completely blocked by PK2 receptor antagonist. The potentiation was also abolished by intracellular dialysis of GF109203X, a protein kinase C inhibitor, or FSC-231, a protein interacting with C-kinase 1 inhibitor. Moreover, PK2 enhanced the acid-evoked membrane excitability of rat dorsal root ganglion neurons and caused a significant increase in the amplitude of the depolarization and the number of spikes induced by acid stimuli. Finally, PK2 exacerbated nociceptive responses to the injection of acetic acid in rats. Conclusion These results suggest that PK2 increases the activity of acid-sensing ion channels via the PK2 receptor and protein kinase C-dependent signal pathways in rat primary sensory neurons. Our findings support that PK2 is a proalgesic factor and its signaling likely contributes to acidosis-evoked pain by sensitizing acid-sensing ion channels.